Functional Divergence of APETALA1 and FRUITFULL is due to Changes in both Regulation and Coding Sequence - McCarthy, Elizabeth W.; Mohamed, Abeer; Litt, Amy (Frontiers in Plant Science, 2015)
Gene duplications are prevalent in plants, and functional divergence subsequent to duplication may be linked with the occurrence of novel phenotypes in plant evolution. Here, we examine the functional divergence of Arabidopsis thaliana APETALA1 (AP1) and FRUITFULL (FUL), which arose via a duplication correlated with the origin of the core eudicots. Both AP1 and FUL play a role in floral meristem identity, but AP1 is required for the formation of sepals and petals whereas FUL is involved in cauline leaf and fruit development. AP1 and FUL are expressed in mutually exclusive domains but also differ in sequence, with unique conserved motifs in the C-terminal domains of the proteins that suggest functional differentiation. To determine whether the functional divergence of AP1 and FUL is due to changes in regulation or changes in coding sequence, we performed promoter swap experiments, in which FUL was expressed in the AP1 domain in the ap1 mutant and vice versa. Our results show that FUL can partially substitute for AP1, and AP1 can partially substitute for FUL; thus, the functional divergence between AP1 and FUL is due to changes in both regulation and coding sequence. We also mutated AP1 and FUL conserved motifs to determine if they are required for protein function and tested the ability of these mutated proteins to interact in yeast with known partners. We found that these motifs appear to play at best a minor role in protein function and dimerization capability, despite being strongly conserved. Our results suggest that the functional differentiation of these two paralogous key transcriptional regulators involves both differences in regulation and in sequence; however, sequence changes in the form of unique conserved motifs do not explain the differences observed.